Peran Manajemen Dalam Membangun Budaya Organisasi Yang Kuat Melalui Kepribadian dan Nilai - Muh. Khotibul Umam; Muhammad Sidiq Purnomo (Jurnal Pendidikan Indonesia (JOUPI), 2024)
Organizational culture has long been recognized as one of the most valuable assets of an organization. A strong culture can be the difference between a successful organization and a failed one. The values, norms, and beliefs held collectively by members of an organization serve as a compass that guides the actions and decisions of each individual. For example, if integrity is held in high regard, then the policies made should reflect transparency and accountability. Policies and procedures provide guidance on the behavior expected of employees. A strong organizational culture is a valuable asset for any company. Management plays a central role in building and maintaining this culture. By addressing various challenges, management can create a positive and productive work environment. The method of writing this article is based on qualitative research with a literature review design, also known as library research. Reviewing the literature in accordance with the theories discussed in the field of educational management. The goal is to gain a comprehensive understanding of a topic, identify research trends, and build a theoretical framework for further research. The results of this study indicate that the congruence of values ​​between individuals and organizations is an important factor in building a healthy and productive organizational culture. Meanwhile, organizations also have values ​​embedded in their culture and business goals, such as innovation, sustainability, or profitability. Differences in values ​​between individuals and organizations are natural.